MBRS-16. MYC REGULATED LONG NONCODING RNA LNC-HLX-2–7 IS A PUTATIVE MOLECULAR MARKER AND A THERAPEUTIC TARGET FOR GROUP 3 MEDULLOBLASTOMAS IN CHILDREN. (4th December 2020) - Katsushima, Keisuke; Joshi, Piyush; Stapleton, Stacie; Garancher, Alexandra; Vibhakar, Rajeev; Raabe, Eric; Eberhart, Charles; Wechsler-Reya, Robert; Jallo, George; Perera, Ranjan
Abstract: Medulloblastoma (MB), a central nervous system tumor that predominantly affects children, requires aggressive therapy. Recent advances in the noncoding RNA genome could contribute to the sub-classification of medulloblastoma. The focus of this study is to identify novel long noncoding RNAs (lncRNAs) as molecular markers and potential therapeutic targets within each subgroup of MBs, in particular within Group 3. We analyzed publicly available 175 RNA-seq datasets to identify a group of putative lncRNA signatures that may be able to differentiate medulloblastoma subgroups accurately. Among those, lncRNA lnc-HLX-2–7 was highly upregulated in Group 3 MB cell lines, patient-derived xenografts, FFPE samples compared to other groups. CRISPR/Cas9 deletion of the lnc-HLX-2–7 followed by the fluorescence-activated sorting and generating monoclonal Group 3 MB cells significantly reduced the cell growth and 3-D colony formation together with the induction of apoptosis. Intracranial injection to mouse cerebellum using lnc-HLX-2–7 deleted cells resulted in reduced tumor growth compared to parental cells, and tumors were further characterized by single-cell sequencing. We identified that oncogene MYC regulates lnc-HLX-2–7 and its expression can be controlled by the small molecule JQ1, a BET-bromodomain (BRD4) inhibitor that disrupts interactions with MYC. RNA-FISH analysis using FFPE, PDX, and tissue microarrays revealed that lnc-HLX-2–7 expression is specific to Group 3 MB compared to other groups. We present supporting evidence that lnc-HLX-2–7 is a novel molecular marker and a potential therapeutic target for Group 3 MBs in children.